Impact of histologic subtype on cancer-specific survival in patients with renal cell carcinoma and tumor thrombus - Tilki, Derya; Nguyen, Hao G.; Dall’Era, Marc A.; Bertini, Roberto; Carballido, Joaquín A.; Chromecki, Thomas; Ciancio, Gaetano; Daneshmand, Siamak; Gontero, Paolo; Gonzalez, Javier; Haferkamp, Axel; Hohenfellner, Markus; et al. (European urology, 2014)
Background - Although different prognostic factors for patients with renal cell carcinoma (RCC) and vena cava tumor thrombus (TT) have been studied, the prognostic value of histologic subtype in these patients remains unclear. - Objective - We analyzed the impact of histologic subtype on cancer-specific survival (CSS). - Design, settings, and participants - We retrospectively analyzed the records of 1774 patients with RCC and TT who underwent radical nephrectomy and tumor thrombectomy from 1971 to 2012 at 22 US and European centers. - Outcome measurements and statistical analysis - Multivariable ordered logistic and Cox regression models were used to quantify the impact of tumor histology on CSS. - Results and limitations - Overall 5-yr CSS was 53.4% (confidence interval [CI], 50.5-56.2) in the entire group. TT level (according to the Mayo classification of macroscopic venous invasion in RCC) was I in 38.5% of patients, II in 30.6%, III in 17.3%, and IV in 13.5%. Histologic subtypes were clear cell renal cell carcinoma (cRCC) in 89.9% of patients, papillary renal cell carcinoma (pRCC) in 8.5%, and chromophobe RCC in 1.6%. In univariable analysis, pRCC was associated with a significantly worse CSS (p<0.001) compared with cRCC. In multivariable analysis, the presence of pRCC was independently associated with CSS (hazard ratio: 1.62; CI, 1.01-2.61; p<0.05). Higher TT level, positive lymph node status, distant metastasis, and fat invasion were also independently associated with CSS. - Conclusions - In our multi-institutional series, we found that patients with pRCC and vena cava TT who underwent radical nephrectomy and tumor thrombectomy had significantly worse cancer-specific outcomes when compared with patients with other histologic subtypes of RCC. We confirmed that higher TT level and fat invasion were independently associated with reduced CSS.
Published online ahead of print on July 10, 2013
Gesehen am 24.07.2020